Overview and Risk Factors of Hypertension in Students at SMPN 35 Semarang - Muhammad Raffa Mulia Nugroho; Azhar Tegar Aldina; Dwi Natasya Rahma Aulya; Rubinem Rubinem; Nor Amalia Muthoharoh (Dian Nuswantoro Semarang, 2026)
Hypertension is one of the main risk factors for cardiovascular disease, which has long been associated with adulthood, but in recent years it has been increasingly found in adolescents. This condition is a major concern because hypertension in adolescents is often asymptomatic and has the potential to continue into adulthood. This study aims to describe the incidence of hypertension and its risk factors at SMPN 35 Semarang. This study aims to describe the prevalence of hypertension and its risk factors at SMPN 35 Semarang. The study used a descriptive quantitative method, utilizing secondary data from routine student health screenings obtained from the Semar PKG 79 system and the Sehat Indonesiaku application. Data analysis was performed descriptively and presented in the form of frequency distributions and percentages. The results of the study showed that students with blood pressure above normal, ranging from prehypertension to grade 1 and 2 hypertension, were found in all grade levels. In addition, risk factors that could potentially contribute to increased blood pressure were found, such as low physical activity, the presence of overweight and obesity, and high exposure to cigarette smoke among students. The conclusion of this study indicates that hypertension has emerged since adolescence, thus requiring the strengthening of routine health screening in schools as well as school-based promotive and preventive efforts to prevent noncommunicable diseases from an early age.